Role of PIM2 in allergic asthma - Du, Wei (Mol Med Rep, 2017)
T cell-associated inflammation, particularly type 2 inflammation, has an important role in asthma pathogenesis, which is suppressed by regulatory T cells (Tregs). Proviral integration site for Moloney murine leukemia virus 2 (PIM2), a member off the serine/threonine kinase family, promotes the growth and survival of T cells and influences the function of Treg cells. However, whether PIM2 affects asthma pathogenesis remains unclear. Peripheral blood mononuclear cells and Treg cells from asthmatic and healthy subjects were obtained, and the expression level of PIM2 was measured by reverse transcription-quantitative polymerase chain reaction and immunocytochemistry. In addition, BALB/c female mice sensitized and challenged by ovalbumin were used as an asthma model, and PIM2 inhibitor was injected during the challenge period to observe the effect of PIM2 on asthma. The asthma symptoms were recorded, and airway hyper-responsiveness (AHR), expression levels of cytokines in the serum or bronchoalveolar lavage fluid (BALF), and the number of BALF leukocytes were evaluated. In addition, hematoxylin and eosin staining and immunohistochemistry of lung tissues was performed. The results demonstrated that PIM2 was overexpressed in patients with asthma in natural Treg cells. Inhibition of PIM2 attenuated asthma symptoms, and improved AHR and airway inflammation compared with asthmatic mice without inhibition of PIM2. In addition, expression levels of interleukin (IL)-10 and forkhead box protein 3 (FOXP3) in BALF were increased following PIM2 inhibition (IL-10, 470.3±21.78 vs. 533.7±25.55 pg/ml, P<0.05; FOXP3, 259±4.68 vs. 279.3±3.68 pg/ml; asthma and PIM2 inhibition groups, respectively; P<0.05). In conclusion, PIM2 may exhibit an important role in asthma pathogenesis and exacerbate AHR, airway inflammation and asthma symptoms. These effects of PIM2 may be dependent on Treg cells and the secretion of IL-10 by Tregs. The results of the present study suggest that PIM2 may be a potential target molecule for asthma treatment.